Voicing Contrast Difficulties in Indonesian EFL Pronunciation - Reza Bakhrun Fidianto Pade; Ari Purnawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Pronunciation remains an important issue in English as a Foreign Language (EFL) learning because unclear sound production may affect students’ spoken intelligibility and confidence in oral communication. This study examines segmental pronunciation errors made by Indonesian EFL students in pronouncing certain words. The study employed a descriptive qualitative design involving English Department students at Universitas Negeri Gorontalo. The data were collected through students’ recorded reading of an English text and supported by semi-structured interviews to explore the possible causes of the errors. The pronunciation data were analyzed by identifying, classifying, and interpreting the students’ sound production based on pronunciation error categories, while the interview data was used to strengthen the interpretation of the findings. The results showed that the students frequently substituted voiced consonants with voiceless sounds, particularly /v/ with /f/, /d/ with /t/ or omission in final position, and /z/ with /s/. These errors indicate that voicing contrast remains challenging for Indonesian EFL learners, especially when the target sounds appear in unfamiliar words or in positions that are less common in Indonesian phonological patterns. The interview findings further revealed that unfamiliar vocabulary, limited pronunciation exposure, lack of practice, and difficulty distinguishing similar sounds contributed to the students’ pronunciation errors. The study concludes that pronunciation instruction should give more explicit attention to segmental contrasts, especially voiced and voiceless consonants, to support clearer and more intelligible spoken English among Indonesian EFL learners.